2015
DOI: 10.1007/s00792-015-0782-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adaptation and salt stress response of Halobacterium salinarum cells revealed by neutron spectroscopy

Abstract: Halobacterium salinarum is an extreme halophile archaeon with an absolute requirement for a multimolar salt environment. It accumulates molar concentrations of KCl in the cytosol to counterbalance the external osmotic pressure imposed by the molar NaCl. As a consequence, cytosolic proteins are permanently exposed to low water activity and highly ionic conditions. In non-adapted systems, such conditions would promote protein aggregation, precipitation, and denaturation. In contrast, in vitro studies showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
1
24
0
3
Order By: Relevance
“…As discussed previously, the molecular dynamic state of the cellular proteome represents a robust indicator of cellular fitness 14,15,31 . Macromolecular denaturation through unfolding leads to lower effective force constants indicating less rigid structures.…”
Section: In Vivo Molecular Dynamics Parameters In Low Salt Stressed Amentioning
confidence: 93%
See 2 more Smart Citations
“…As discussed previously, the molecular dynamic state of the cellular proteome represents a robust indicator of cellular fitness 14,15,31 . Macromolecular denaturation through unfolding leads to lower effective force constants indicating less rigid structures.…”
Section: In Vivo Molecular Dynamics Parameters In Low Salt Stressed Amentioning
confidence: 93%
“…In the case of Hbt. salinarum we have shown that below 2 M NaCl (a value which induces unfolding of the model Haloarcula marismortui enzyme, MalDH, in absence of cofactors) halophilic cells suffer a high mortality rate 15 . In the same study, molecular dynamics parameters of the proteome were measured in vivo by neutron scattering for cultures exposed to various lower salt concentrations.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, only few of them were studied so far by means of incoherent neutron scattering, among them Escherichia coli 78 ( E. coli ), Haloarcula marismortui 9, red blood cells10, Halobacterium salinarum 1112 and very recently Shevanella Oneidensis 13. The advantages of neutron scattering consist in the huge incoherent cross section of hydrogen with respect to other atoms present in biological samples, which allows studying cellular constituents8 as well as water dynamics14, and in the fact that unlike X-rays, thermal neutrons have such a low energy that they do not induce radiation damage to the sample.…”
mentioning
confidence: 99%
“…Em bactérias, a expressão diferencial de seus membros é associado com mecanismos de regulação pós-transcricionais(Owolabi e Rosen, 1990).Baseados nos estudos feitos por Beer e col, onde foram examinadas variações na composição do meio CM padrão do crescimento de H. salinarum NRC-1(Beer, Wurtmann e Baliga, 2014), testamos duas composições distintas: 86% de sais em relação ao meio CM (meio A), e 72% (meio B). A diminuição de sais no meio de crescimento de H. salinarum NRC-1 promovem mudanças nas taxas de crescimento, na morfologia da célula, conteúdo de vesículas de gás e regulação de genes vinculados ao metabolismo anaeróbico(Beer, Wurtmann e Baliga, 2014;Vauclare et al, 2015).No meio A, observamos que a partir de 50 horas de crescimento a linhagem nocaute apresenta menor OD 600nm do que a linhagem controle (Figura 4.8). Isto pode indicar uma maior sensibilidade a variações na concentração de sal na transição entre as fases exponencial e estacionária do crescimento, onde o metabolismo de H. salinarum NRC-1 pode mudar de Porém, só se detectam pequenas diferenças entre as linhagens a partir das 91 horas (Figura 4.8).…”
unclassified